Prooxidant–antioxidant balance, advanced oxidation protein products and lipid peroxidation in Serbian patients with Parkinson's disease. (3rd July 2018) - Miletić, Jadranka; Drakulić, Dunja; Pejić, Snežana; Petković, Marijana; Ilić, Tihomir V.; Miljković, Milica; Stefanović, Aleksandra; Prostran, Milica; Stojanov, Marina
ABSTRACT: Background: Biomarkers of oxidative stress are relevant in the evaluation of the disease status and prooxidant–antioxidant balance, advanced oxidation protein products and lipid peroxidation products (malondialdehyde and 4-hydroxynonenal) are being extensively evaluated regarding their relationship with clinical presentation and disease severity. Aim of the study: The aim of this study was to evaluate the levels of the above-mentioned parameters in plasma of 39 men and 17 women with Parkinson's disease, originated from the Republic of Serbia and their relation to clinicopathological characteristics (gender, age at examination, duration of the disease, and Hoehn and Yahr score) and oxidative status. Results: The incidence of disease was 2:1 towards males. The investigated oxidative parameters were gender and Hoehn and Yahr related. Significant association of higher Hoehn and Yahr scores was observed for malondialdehyde ( p = 0.01) and prooxidant–antioxidant balance ( p = 0.02). Relation between oxidant–antioxidant status was further supported by observed positive correlation between 4-hydroxynonenal ( p = 0.04) and prooxidant–antioxidant balance ( p = 0.03). Finally, the multivariate analysis indicated that prooxidant–antioxidant balance and malondialdehyde were partially determined by gender (10.6% and 7.6%) and Hoehn and Yahr scores (13.6% and 18.8%), while Hoehn and Yahr scores contributed to the variance of advanced oxidation protein products with 13.2%. Conclusion: Our results indicate the higher level of oxidative stress (oxidant–antioxidant imbalance) and possible relation of several markers with gender and disease stage in patients with Parkinson's disease. The analyzed markers could be used to specify the severity of oxidative stress; however, their potential value should be analyzed in further studies. Abstract :